Interstitial ectopic pregnancy in a 41-year-old woman: a case report - Pawłowicz, Paweł; Massalska, Diana; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2012)
Cornual pregnancy is a rarely occurring variant of ectopic pregnancy with often unspecific symptoms, what makes the diagnosis very difficult. Its early detection is a key factor for using less invasive treatment and preserving fertility. The article presents a case of a 41-year-old nullipara in her fourth pregnancy, after unilateral resection of adnexa because of the tubal pregnancy, with the diagnosis of the cornual pregnancy. She was treated laparoscopically, i.e. the cornual resection was performed. The postoperative period was uneventful. Early diagnosis and treatment made it possible to minimize the risk connected with this life-threatening entity.